ANALISIS PENGARUH SISTEM PEMBAYARAN TERHADAP KEUNTUNGAN PROYEK - Budi Adi Dharma Siregar; Ardiansyah Ardiansyah (ITB Ahmad Dahlan Jakarta, 2022)
The implementation of construction development is strongly influenced by the payment sistem implemented. The contractor as the executor of construction activities with predetermined costs, will definitely suppress the implementation costs that will be issued in various ways through financial management, including based on the payment sistem carried out. The research was conducted on the Al Ukhuwah Mosque construction project, which is located in the Avany complex, BSD, Banten. The study was conducted by an experimental cash flow analysis with a 25% and 50% down payment sistem, using the PDM method with EST conditions. The results obtained from the 2 experiments show that a job with a 50% down payment will provide a profit of 12,01% or an overdraft value of Rp. 79.250.000,-.